Programming changes in GLUT1 mediated the accumulation of AGEs and matrix degradation in the articular cartilage of female adult rats after prenatal caffeine exposure. (January 2020) - Qing-xian, Li; Lin-long, Wang; Yi-zhong, Wang; Liang, Liu; Hui, Han; Liao-bin, Chen; Hui, Wang
Graphical abstract: Highlights: PCE female fetus suffered articular cartilage dysplasia. PCE promoted AGEs accumulation and matrix degradation in cartilage of adult offspring. The GC-IGF1-GLUT1 axis mediated susceptibility to OA in PCE offspring. Abstract: Osteoarthritis is associated with intrauterine growth retardation (IUGR) and abnormal glucose metabolism. Our laboratory previously reported that prenatal caffeine exposure (PCE) can induce intrauterine maternal glucocorticoid (GC) overexposure in IUGR offspring and increase susceptibility to osteoarthritis after birth. In the present study, we demonstrated the essential role of glucose transporter 1 (GLUT1) programming changes in the increased matrix degradation of articular cartilage and susceptibility to osteoarthritis in female PCE adult offspring. In vivo, we found that PCE decreased the matrix content but did not significantly change the expression of matrix degradation-related genes in the articular cartilage of female fetal rats. The decreased expression of IGF1 and GLUT1 and the content of advanced-glycation-end-products (AGEs) were also detected. At different postnatal stages (2, 6, and 12 weeks), the cartilage matrix content decreased while the degradation-related genes expression increased in the PCE group. Meanwhile, the expression of IGF1 and GLUT1 and AGEs content in the local cartilage increased. In vitro, the expression levels of IGF1 and GLUT1 were inhibited by corticosterone but remained unchanged under caffeine treatment. Exogenous IGF1 can reverse the corticosterone-induced decrease in GLUT1 expression and promote AGEs production, while mifepristone (a glucocorticoid receptor inhibitor) reversed the corticosterone-induced low expression of IGF1 and GLUT1. Exogenous AGEs can increase the expression of inflammatory factors (IL-6 and TNF-α) and degradation-related genes, and decrease the matrix synthesis-related genes expression in chondrocyte. In conclusion, the GC-IGF1-GLUT1 axis mediated intrauterine dysplasia of articular cartilage, increased accumulation of AGEs and matrix degradation after birth in PCE female offspring, thereby increasing their susceptibility to osteoarthritis in adulthood.